2018
DOI: 10.1186/s13014-018-1133-8
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated vs. conventionally fractionated adjuvant radiotherapy in high-risk head and neck cancer: a meta-analysis

Abstract: BackgroundAdjuvant radiotherapy in advanced head and neck squamous cell cancer (HNSCC) reduces the risk of local-regional failure and most likely increases the survival rate. Patients at high risk for tumor recurrence may benefit from more aggressive altered fractionation schedules in order to reduce the overall time from surgery to completion of radiotherapy. Here, we reviewed the results of six randomized trials addressing the above hypothesis.MethodsIn the six trials of interest, a total of 988 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Depending on tumor localization the absolute survival advantage is between four to 9 % [2]. Beyond that, additional induction chemotherapy prior to concurrent CRT or acceleration of radiotherapy did not improve outcome [1113].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on tumor localization the absolute survival advantage is between four to 9 % [2]. Beyond that, additional induction chemotherapy prior to concurrent CRT or acceleration of radiotherapy did not improve outcome [1113].…”
Section: Discussionmentioning
confidence: 99%
“…An additional five eligible studies were added, including four that were published after the cut-off date of 01/10/2019 [15][16][17][18] and one randomized trial that was not identified through the literature search. 19 Studies with primary oncologic endpoints are shown in Table S1 and included 11 systematic reviews, [20][21][22][23][24][25][26][27][28][29][30] 24 randomized trials with four long-term updates, 19,31-57 29 nonrandomized clinical trials, [15][16][17][18] and nine post hoc analyses of randomized trials. [83][84][85][86][87][88][89][90][91] The randomized trials are presented in Table 4.…”
Section: Characteristics Of Studies Identified In the Literature Sementioning
confidence: 99%
“…Single‐arm prospective 76,79,81 and randomized studies 23,24,51 demonstrated that altered fractionation increases acute toxicities, such as mucositis, dermatitis and feeding‐tube use during treatment. The effects on late toxicity have varied, but at least one study showed an increase in late toxicity 23,24,34 …”
Section: Topic 1: Summary Of Studies With Oncologic Endpointsmentioning
confidence: 99%
“…A Phase III study comparing accelerated versus fractionated postoperative radiotherapy for advanced head and neck cancer did show a trend for improved locoregional control for patients who had a delay in starting radiation, but otherwise no significant differences were seen between the control and experimental arms (30). One meta-analysis of six trials involving more than 900 patients with locally advanced HNSCC found that accelerated radiation therapy did not improve loco-regional control, progression-free survival, or overall survival (32). In fact, the meta-analysis found that accelerated radiation therapy schedules were associated with higher rates of acute mucositis.…”
Section: Current Guidelines For Postoperative Treatmentmentioning
confidence: 99%